Economic Activity in Context of Regions, Education Level, Age Group and Gender: Case of Latvia - Sloka, Biruta; Čipāne, Kate (University of Latvia, 2019)
In the National Development Plan of Latvia 2014–2020 it is written that society is aware that social, regional and opportunity inequalities can be reduced by a high overall employment rate in which everyone seeks for productivity. High employment rate is important not only for decreasing inequalities in country, but also for promoting economic growth. There have always been employment challenges in Latvia that are complex and insufficiently researched in academic research. The aim of the study is to analyse economic activity in Latvia by regions, education level, age group and gender. Research methods used in preparation of the article: scientific publication and previous conducted research results analysis, analysis of Labour Force Survey results (in 2014–2017) which are compared with the results of other European Union and OECD countries. Survey results are analysed using indicators of descriptive statistics (indicators of central tendency or location – arithmetic mean, mode, median), indicators of variability (indicators of dispersion – range, standard deviation and standard error of mean), cross-tabulations by regions in Latvia, by level of education, by age group, by gender and analysis of variance – ANOVA are used. The results of analysis indicated that the highest unemployment rate is in Latgale region and the higher the level of education, the less likely it is to be unemployed in Latvia.
Keywords: Latvia; economic activity; employment; employees; labour force; regional development; unemployment; Research Subject Categories::SOCIAL SCIENCES::Business and economics